EVALUASI RASIONALITAS PENGGUNAAN ANTIBIOTIK PASIEN PNEUMONIA DI RS TIPE B KOTA BOGOR - Septiani, Wulan; Rosiana, Rosiana; Dewi, Masita Sari; Marselina, Marselina (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Pneumonia remains one of the leading causes of morbidity and mortality worldwide. Inappropriate use of antibiotics can increase the risk of bacterial resistance. Rationality evaluation is essential to ensure appropriate selection, dosage, and duration of therapy. This study aimed to describe the characteristics of pneumonia patients, antibiotic prescribing patterns, and their rational use in the inpatient ward of Type B Hospital in Bogor City in 2024. A retrospective descriptive design was employed using medical records of 83 pneumonia patients from January to December 2024. Data were analyzed descriptively, and rationality was assessed using the Gyssens method based on the Ministry of Health Regulation No. 28 of 2021. The results showed that most patients were aged ≥60 years (41.0%) and male (51.8%). The most commonly used antibiotics were ceftriaxone (57.9%) and levofloxacin (20.0%). Category 0 (appropriate) accounted for 55.6%, while 44.4% were inappropriate, mainly IVa (23.3%) and IIIb (10.0%). Conclusion: Improving rationality requires regular evaluation, clinical pathways, and antimicrobial stewardship programs.